An Efficient Revocable Identity-Based Encryption with Equality Test Scheme for the Wireless Body Area Network. (13th August 2022) - Tsai, Tung-Tso; Lin, Han-Yu; Chang, Hsiao-Chieh
Abstract : With the rapid development and popularization of cloud computing, people are willing to upload their own data to the cloud to enjoy the services. However, some personal and private data are not suitable for uploading directly to the cloud. Therefore, these data must be encrypted before uploading to the cloud to ensure the confidentiality. To achieve the confidentiality of data and enjoy cloud services, a notion of identity-based encryption with equality test (IBEET) was proposed. Using IBEET, two ciphertexts encrypted under different public keys can be tested to confirm whether they contain the same plaintext. The equality test can be applied to the wireless body area network system in which the cloud can utilize ciphertexts from patients and medical institutions to perform equality tests to determine whether which patient's status is abnormal. Indeed, revoking illegal or expired users on any cryptosystem is an important issue. To the best of our knowledge, there is little research on the design mechanism of user revocation in the IBEET. In this paper, we propose a novel notion of revocable identity-based encryption with an equality test, called RIBEET. Based on the notion, we present the first RIBEET scheme. Meanwhile, the proposed scheme will be proven to be secure under the bilinear Diffie-Hellman (BDH) assumption.